2016
DOI: 10.13189/ujer.2016.040103
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Science Teachers' Views on Laboratory Applications in Science Education: The Effect of a Two-semester Course

Abstract: The aim of this study was to examine pre-service science teachers' views about laboratory applications in science education and how their views changed through laboratory applications that were carried out for two semesters. 63 (52 females, 11 males) pre-service teachers participated in the study. The study was carried out by using pre-test and post-test design. Data was collected on the differences between the views of pre-service science teachers before and after laboratory courses. For data collection, teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
17
0
2
Order By: Relevance
“…These findings are largely in line with previous studies addressing professional development among science teachers (Noh, Cha, Kang, & Scharmann, 2004;Alshehry, 2009;Harman et al, 2016). We found that the participating teachers lack some basic knowledge and experience (e.g., self-development to improve their teaching style, the lack of using some new facilities and updates the methods of teaching, not being able to proving their opinions suggested in their decision made).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are largely in line with previous studies addressing professional development among science teachers (Noh, Cha, Kang, & Scharmann, 2004;Alshehry, 2009;Harman et al, 2016). We found that the participating teachers lack some basic knowledge and experience (e.g., self-development to improve their teaching style, the lack of using some new facilities and updates the methods of teaching, not being able to proving their opinions suggested in their decision made).…”
Section: Discussionsupporting
confidence: 91%
“…For the continued professional development of teachers, it will be necessary to develop critical, analytical, evaluation and reflective corporations with a good knowledge and understanding of teaching practices (Ian Terrell, 2003). Most professional development inactivates involving science teachers have focused on laboratory sessions, experimental learning, and naturalization of theoretical information by application and observational methods (Harman et al, 2016). This will be explored by the second levels of master's programme among science colleges in the current positions which have not been explored by other international or national studies before.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the current study, some of the class teachers received laboratory lessons during their undergraduate education, some of them received in-service training after they started to work, and some of them were trained as science teachers in different branches. Teacher training shall encourage the teacher candidates to understand the nature of practice and help them use these activities in their classes in the future [5]. In the study conducted by [34], it is stated that teachers generally find themselves adequate in carrying out their laboratory practices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In a different study conducted by [37], it is stated that laboratory practices are effective for students to gain a scientific perspective. Furthermore, based on their findings arising from teachers' views, it is claimed that laboratory practices enable effective, permanent and enjoyable learning [5].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation